Examining Online Traffic Patterns to Popular Direct-To-Consumer Websites for Evaluation and Treatment of Erectile Dysfunction. Issue 1 (8th January 2021) - Wackerbarth, Joel J.; Fantus, Richard J.; Darves-Bornoz, Annie; Hehemann, Marah C.; Helfand, Brian T.; Keeter, Mary Kate; Brannigan, Robert E.; Bennett, Nelson E.; Halpern, Joshua A.
Abstract: Background: Direct-to-consumer (DTC) Internet-based prescription and pharmacy platforms offer electronic consultation for evaluation and pharmacologic treatment of erectile dysfunction (ED) without a physical exam or in-person visit, presenting a potentially dramatic shift in care for this condition. Aim: To characterize the extent to which DTC prescribing sites for ED generate traffic and attract individual users. Methods: Using SEMRush, a marketing software platform that provides analytics regarding website traffic, we examined online site visits to 6 major DTC prescribing websites offering ED evaluation and treatment from October 2017 through December 2019. Outcomes: We recorded trends in the number of unique visitors over time, visitor referral patterns, and the proportion of overall visitors to individual sites. Results: During the study period, the total number of unique, quarterly visitors increased by 1, 688% from 655, 733 in the 4th quarter (Q4) 2017 to over 11 million in Q4 2019. In 2019, there were on average 4, 971, 674 visits to all sites combined each month. For the 2 largest sites (Hims and Roman), visitors predominantly reached the site via direct web address (27.3%) or search engine referral (27.3%). Clinical implications: An increasingly large number of potential patients are utilizing DTC prescribing platforms for the diagnosis and treatment of ED, which do not require physical exams or treatment of other comorbid conditions. Strength & Limitations: Demonstrates high demand for ED DTC prescribing services using independent market research software and characterizes the number of visits for the first time. Limitations include the lack of individual demographics and lack of information regarding what proportion of unique visits lead to evaluation and treatment using the services. Conclusion: The dramatic increase in visits to DTC prescribing sites that treat ED represents a paradigm shift in ED care, and it is imperative that clinicians and researchers work to understand how patients utilize online telemedicine, the safety and efficacy of online management of ED, and the potential downstream implications of its widespread use.